Experimental investigation on sealing efficiency of CNT composite grouts in inclined fractures with flowing water. (8th February 2021) - Liu, Yaohui; Zhang, Lei; Yang, Ping; Wei, Xiao
Highlights: SE of CNT composite grouts in inclined fracture with flowing water was investigated. Inclination angle of fracture plays a crucial role in flowing water grouting. CNT composite grouts are applicable for flowing water grouting in inclined fracture. Silica fume improve SE of CNT composite grouts. Abstract: A series of physical simulation tests were conducted to investigate performance of carbon nanotube (CNT) composite grouts in inclined fracture grouting with flowing water. The viscosity of grouts increases with an increase of CNTs content. Silica fume can improve the dispersion of CNTs and maximal fluid pressure of CNT composite grouts. Orthogonal experimental results shows that sealing efficiency (SE) of CNT composite grouts increases with an increase of CNTs and a decrease of initial flowing rate. Slight inclination can improve the SE of CNT composite grouts and superfluous silica fume has limited effects on SE.